2020
DOI: 10.1016/j.bbmt.2020.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Smoking on Outcomes of Allogeneic Transplantation: A Single-Center Analysis

Abstract: Pulmonary complications are fatal adverse events after allogeneic hematopoietic cell transplantation (allo-HCT). On the other hand, smoking is a well-known risk factor for various pulmonary diseases and also increases the incidence of pulmonary complications and overall mortality in allo-HCT recipients. In this study, we retrospectively assessed the impact of smoking intensity on survival outcomes. This study included consecutive allo-HCT recipients at our center between June 2007 and May 2019 whose smoking pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…27 As for male as a risk factor, smoking might affect the outcomes. 34 There are some limitations in this study. First, CMV antigenemia has been used in Japan because of their preference of the health insurance system, whereas real-time PCR has been more commonly used worldwide.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…27 As for male as a risk factor, smoking might affect the outcomes. 34 There are some limitations in this study. First, CMV antigenemia has been used in Japan because of their preference of the health insurance system, whereas real-time PCR has been more commonly used worldwide.…”
Section: Discussionmentioning
confidence: 91%
“…Aside from CMV‐AUC, well‐recognized factors such as older age and disease risk were identified as risk factors for poor OS 27 . As for male as a risk factor, smoking might affect the outcomes 34 …”
Section: Discussionmentioning
confidence: 99%
“…Although it has been observed that smokers tend to exhibit reduced posttransplant survival rates and increased mortality following allogeneic HSPC transplantation [30][31][32][33], the potential role of impaired hematopoietic niche function has not been explored in depth. We conducted a comprehensive analysis of the influence of CSE on MSC characteristics and MSC-HSPC interactions.…”
Section: Discussionmentioning
confidence: 99%